Suicide terrorism: what, where, when and how in Pakistan. (1st March 2011) - Bhatti, J A; Mehmood, A; Shahid, M; Bhatti, S A; Akhtar, U; Razzak, J A
Abstract : Introduction: Terrorism in which violence is intentionally directed at civilian targets has indeed become a major cause of morbidity and mortality in some Eastern Mediterranean countries. The aim of this study was to assess the burden and factors associated with this problem in Pakistan. Method: Information about suicide-terrorism related events, deaths and injuries was extracted from South-Asian Terrorism Portal for the period from 2002 to October 2009. Results: Out of 198 events, civilians were involved in 194 events. Civilian accounted for 74.1 (N=2017) of those died and 93.8% (N=6129) of those injured. In nine districts mortalities were more than 1 death per 100 000 inhabitants per year. Yearly trend showed a shift of attack targets from foreigners and sectarian in 2002–2005 periods toward security forces or general public in 2006–2009 periods. Attacks carried out on public installations (mosque) or gatherings (political) resulted in significantly high (p≤0.02) number of deaths (22 vs 8) and injuries (59 vs 24) per event as compared to security installations. Conclusion: Civilian mortalities were 10 times or higher in Pakistani districts than that reported due to such mechanism in USA during 1994–2002 period. Prevention might focus on political negotiation with armed groups and taking appropriate measures for protection of mosques and political gatherings.